The Importance of Positionality for Qualitative Researchers - Gurr, Hannah; Oliver, Louise; Harvey, Orlanda; Subedi, Madhusudan; van Teijlingen, Edwin (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Qualitative researchers are required to be critically reflective and explain to readers their positionality on their work. This account can be relatively straightforward, but there are occasions when this process of reflection and outlining one’s positionality is much more complicated. This method-paper explains this process. It outlines, using examples of different occasions and situations, where and why such complications may arise, for example, around values and personal experiences. It concludes with further practical advice on writing the section on positionality for novice social scientists.